Unavoidable online education due to COVID-19 and its association to computer vision syndrome: a cross-sectional survey. Issue 1 (30th September 2022) - Roy, Simanta; Sharif, Azaz Bin; Chowdhury, Sreshtha; Iktidar, Mohammad Azmain
Abstract : Background: During the COVID-19 pandemic, online education and entertainment have increased significantly due to strict isolation and frequent lockdowns. This study intended to explore the prevalence and potential factors associated with computer vision syndrome (CVS) among the postsecondary students of Bangladesh pursuing online education. Methods: In total, there were 917 postsecondary students participated in this study. Information on sociodemographic variables, and CVS symptom-related variables were collected using a prevalidated self-administered questionnaire. The CVS questionnaire was used to assess an individual's CVS status. The bivariate association between CVS and other categorical variables was obtained using a χ 2 test. A multivariable logistic regression model was used to explore variables associated with the CVS. Results: The overall prevalence of CVS was 68.16%. Most common symptoms were headache (42.4%), feeling of worsening eyesight (23.2%), and eye pain (23.2%). CVS was associated with educational status (p=0.03), family history of eye-related problems (p<0.001), personal history of eye-related problems (p<0.001), usage of eye accessories (p<0.001), type of device used for online education (p<0.01), average daily use (p<0.01), and usage pattern (p=0.02). After adjusting for confounders, CVS was significantly related to the use of mobile or tablet (adjusted OR, AOR 8.954, 95% CI 1.57 to 51.063), continuing online education for more than 12 hours/day without any break or insufficient break (AOR 7.654, 95% CI 1.625 to 36.053), and previous family (AOR 3.189, 95% CI 1.751 to 5.811) or personal history of eye problems or headaches, or insomnia (AOR 6.214, 95% CI 2.783 to 13.878). Conclusion: A high prevalence of CVS was observed among the post-secondary students in Bangladesh. Since an extensive use of digital screens is somewhat unavoidable during unprecedented times, such as COVID-19, educators should include CVS awareness and prevention in their curricula.